Peristaltic transport of two-layered blood flow using Herschel–Bulkley Model. Issue 1 (1st January 2018) - Rajashekhar, C.; Manjunatha, G.; Prasad, K. V.; Divya, B. B.; Vaidya, Hanumesh
Abstract: The present article investigates the peristaltic transport of a Herschel–Bulkley fluid in an axisymmetric tube. The governing equations are solved using the long wavelength and small Reynolds number approximation. The closed-form solutions are obtained and analyzed for the effects of the fluid behavior index, amplitude ratio, and yield stress on pressure, pressure rise, frictional force, and streamlines. The present model reveals that the increase in flux against pressure rise for a Newtonian fluid is less when compared with Herschel–Bulkley fluid. Further, these changes are opposite to the behavior of frictional force against pressure rise. Also, it is noticed that pressure rise for a fixed value of amplitude ratio in Herschel–Bulkley model is more significant than that of a Newtonian, Power-law, and Bingham model. Furthermore, it is observed that, for small values of yield stress, there is not much difference between Herschel–Bulkley and Power-law fluids. GRAPHICAL ABSTRACT: